1996
DOI: 10.1017/s1357729800014284
|View full text |Cite
|
Sign up to set email alerts
|

Keeping growing cattle outside during winter: behaviour, production and climatic demand

Abstract: Keeping cattle inside on concrete slatted floors can be detrimental to their health and behaviour and is also costly. Therefore, 22 steers of the Swedish Red and White Dairy breed were used to investigate the effect of wintering outdoors on growing cattle. The steers had a mean weight of 310 kg at the onset of the study. During winter, 11 ‘indoor’ steers were housed in pens with concrete slatted floors and 11 ‘outdoor’ steers were kept in a field with access to a shelter and trees. From the end of April until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…By lying down on a dry and insulated surface, an animal can save energy, not only because of the lowered costs for locomotion, but also by minimising its body surface exposure which reduces radiation heat loss. Several studies have previously shown that cattle respond to extreme wind and cold by choosing a milder microclimate for resting (Senft et al 1985;Houseal and Olson 1995) and that they spend more time lying during cold days (Gonyou et al 1979;Redbo et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…By lying down on a dry and insulated surface, an animal can save energy, not only because of the lowered costs for locomotion, but also by minimising its body surface exposure which reduces radiation heat loss. Several studies have previously shown that cattle respond to extreme wind and cold by choosing a milder microclimate for resting (Senft et al 1985;Houseal and Olson 1995) and that they spend more time lying during cold days (Gonyou et al 1979;Redbo et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in outdoor or uninsulated conditions, growing cattle often exhibit good performance (e.g. Mossberg et al 1992, 1993, Redbo et al 1996, Manninen et al 2007), but opposite results have also been reported, e.g. by Delfino and Mathison (1991).…”
Section: Introductionmentioning
confidence: 99%
“…Adult reindeer have previously been observed lying curled up during severe frost (Sokolov, 1990). A less active behaviour is a way to conserve energy and has been observed in farmed deer and steers during cold weather (Gilbert & Bateman, 1983;Redbo et al, 1996).…”
Section: Resultsmentioning
confidence: 99%